Energy policy paradox on environmental performance: The moderating role of renewable energy patents. (1st November 2021) - Iqbal, Wasim; Tang, Yuk Ming; Lijun, Ma; Chau, Ka Yin; Xuan, Wang; Fatima, Arooj
Abstract: The environmental and socioeconomic considerations of energy production have become crucial because of the increasingly complex relationship between energy and the environment. This study aims to develop possible mechanisms for perspectives on energy policy and the environment by exploring the mediating role of renewable energy patents. Non-radial data envelopment analysis and panel data models are applied using the panel data from 2010 to 2017 from 30 Chinese provinces. The results show an overall improvement in the environmental performance index (EPI) of China's provinces, but the average EPI is still relatively weak, with an average value between 0.44 and 0.52, which is far below the optimal value 1.. Furthermore, the econometric model offers evidence that provincial renewable energy and emission reduction policies positively impact the enhancement of EPI. The findings have several implications for energy and environmental policies. Highlights: We assess energy policy paradox on environmental performance. We analyze renewable and emission reduction polices on different levels. We investigate renewable energy patents impact on carbon emissions reduction.